Pasar Jawa: Special Area Plan (SAP) for Klang Royal Town, Selangor - Wan Mohamad, Wan Ramlah; Asmawi, M. Zainora; Muhamad, Nur Lili Izyani (Kulliyah of Architecture & Environmental Design, International Islamic University Malaysia, 2019)
The project aims to design the Special Area Plan (SAP) for Pasar Jawa Klang Selangor. The newly proposed J-Market Square Park will be the new commercial area. This market square is designed to create a new landmark and promote tourism activities. The supporting facilities such as pergola, bins, water fountain and lamp post are designed in several designated areas include seating area, eating area, food hub and walkable area.